WMD elimination in Iraq, 2003. Issue 1 (3rd March 2016) - Duelfer, Charles
Abstract : The full picture of Iraq's weapons of mass destruction (WMD) programs became clear after 2003. The Iraq Survey Group (ISG) had extraordinary access to people, documents, and sites. The findings revealed much about Iraq's decision making regarding WMD as well as the success of UN inspection activities. Pre-war errors in process and judgments concerning Iraq's WMD must be considered in the context of the times. This is especially true regarding pre-war intelligence assessments that were based on bad analysis, insufficiently caveated, and grossly wrong. The investigative process of the ISG built on the background of UN inspection teams (the UN Special Commission and its successor, the UN Monitoring, Verification, and Inspection Commission). The unique access the ISG had to Iraqi decision making—including detailed debriefings of Saddam Hussein and all his key lieutenants—provided insight into how the inspected country reacted to international inspections. The window into Saddam's decisions in response to inspections and his future intentions provides important background and lessons relevant to new monitoring regimes.